Behavior of exposed column-base connections with four internal anchor bolts under seismic loading. (December 2021) - Pan, Jianrong; Huang, Ruike; Xu, Jing; Wang, Peng; Wang, Zhan; Chen, Jin
Highlights: Seismic behavior of exposed column-base connections with four internal anchor bolts. Parameter impacts on the initial rotational stiffness of the column-base connection. Predicting the stiffness and capacity of this connection under minor-axis loading. Method to calculate the moment-rotation curve with a three-parameter power function. Abstract: Laboratory experiments were conducted to define the response to earthquake loading of the exposed column-base connections common in low-rise steel frame structures. Six full-scale column-base connections with four internal anchor bolts were prepared and tested to failure under major- and minor-axis cyclic loading. The parameters varied were the size and thickness of the base plate and the diameter of the anchor bolts. The data were used to calibrate a finite element simulation, and that was used to predict the influence of other design parameters on the initial rotational stiffness of a connection. Linear regression was used to model the response surface of the initial rotational stiffness and the bending capacity of the connections under minor-axis loading. A three-parameter power function model was derived which acceptably predicted the experimental results.